Simplify (x+y+z)²-(x-y-z) ²
Answers
Answered by
0
Answer:
2[x*(y+z)]
Step-by-step explanation:
(x+y+z)²-(x-y-z)²
= [x+y+z+(x-y-z] * [x+y+z-(x-y-z)] {a²-b²= (a+b)(a-b)
= [2x] * [x+y+z-x+y+z]
= [2x] * [2y+2z]
= 2[x*(y+z)]
Answered by
0
Step-by-step explanation:
this is the answer of your question
Attachments:
![](https://hi-static.z-dn.net/files/dda/027d0029c7012ab2e36557c045bb2e13.jpg)
Similar questions
India Languages,
4 months ago
Hindi,
4 months ago
Science,
4 months ago
English,
9 months ago
Hindi,
9 months ago
English,
1 year ago
CBSE BOARD X,
1 year ago
Math,
1 year ago